ChemInform Abstract: AlCl3‐Mediated Aldol Cyclocondensation of 1, 6‐ and 1, 7‐Diones to Cyclopentene and Cyclohexene Derivatives. Issue 5 (February 2015) - Miyahara, Yuji; Ito, Yoshio N.
Abstract During the synthesis of diketone (I), a second product appears after 2h which is identified as cyclopentene (II).